HUBUNGAN PERSEPSI REMAJA TENTANG BODY SHAMING TERHADAP PENERIMAAN DIRI DI SMA PATRIOT BEKASI - Arina Amini (2020)
The body shaming treatment is defined as an act to embarrass physical appearence by comming negative or insulting someone about shape, size and color of the body's skin.